Pediatric related risk factors in acute and delayed chemotherapyinduced nausea and vomiting: multivariate analysis - Albuquerque, Ariádne Sousa; Okumura, Lucas Miyake; Betin-de-Moraes, Nelci Rodrigues; Ricieri, Marinei Campos; Barros, Tais Tereziano; Fachi, Mariana Millan (Brazilian Journal of Oncology, 2022)
Objectives: This study aimed to characterize the clinical profile and the factors that predispose chemotherapy-induced nausea and vomiting (CINV) in the acute and delayed phases.Methods: A retrospective cohort study was conducted in a Brazilian hospital with pediatric patients under 18 years old receiving moderately or highly emetogenic chemotherapy. Thus, a descriptive analysis was performed to characterize this population, followed by univariate and multivariate analysis to evaluate the risk factors for CINV. In both phases, considering significant the variables with p-values <0.05.Results: The median age was 6 and 71% of the patients included used highly emetogenic protocols. Furthermore, 41% and 76% did not have vomit in the acute and delayed phase, respectively. Through logistic regression, it is noted that patients with bone tumors and sarcomas have higher CINV in the acute phase (OR 10.0, 95%IC 1.1-88.9, p=0.039), while patients who do not have complete control in the acute phase are more likely to have CINV in the delayed phase (OR 11.8, 95%IC 1.1-130.5, p=0.044).Conclusion: These results suggest that bone tumors and sarcomas are associated with an increase in CINV in the acute phase. In addition, control in the acute phase is associated with a complete response in the delayed phase.
Keywords: Vomiting; Chemotherapy; Pediatric; Oncology; Antiemetics